Comment on "Insight into the reversible structural crystalline-state transformation from MIL-53(Al) to MIL-68.Al)" by A. Perea-Cachero, E. Romero, C. Tellez and J. Coronas, CrystEngComm, 2018, 20, 402 - Hartmann, Martin; Kriesten, Martin; Hoffmann, Kilian (Crystengcomm, 2018)
In a recently published communication (CrystEngComm, 2018, 20, 402-406), Perea-Cachero et al. stated that the topologically isomeric metal-organic frameworks MIL-53(Al) and MIL-68(Al) could be reversibly transformed into each other. However, the suggested synthesis procedure for MIL-68 indeed resulted in MIL-53 with DMF entrapped inside of the pores. The collected PXRD pattern of MIL-53DMF was then inadvertently assigned to the MIL-68 structure.

Comment on "insight into the reversible structural crystalline-state transformation from MIL-53(Al) to MIL-68(Al)" by A. Perea-Cachero, E. Romero, C. Téllez and J. Coronas,: CrystEngComm, 2018, 20, 402 - Kriesten, Martin; Hoffmann, Kilian; Hartmann, Martin (Crystengcomm, 2018)

Elucidation of the Formation Mechanism of Metal-Organic Frameworks via in-Situ Raman and FTIR Spectroscopy under Solvothermal Conditions - Embrechts, Heidemarie; Kriesten, Martin; Hoffmann, Kilian; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (Journal of Physical Chemistry C, 2018)
The metal–organic framework MIL-53(Al) serves as a model system in this study. Its formation mechanism in N,N-dimethylformamide (DMF) is elucidated through simultaneous FTIR and Raman spectroscopy and turbidity measurements collected under in-situ synthesis conditions in a custom-designed solvothermal reactor coupled with reaction sampling. Different synthesis steps are followed over synthesis time including a prenucleation building unit (PNBU) consisting of one linker molecule and one aluminum atom, the assembly of the PNBUs to MIL-53 nuclei in solution, the decomposition of DMF to formic acid and dimethylammonium, and finally the precipitation of the crystalline MOF phase. The rearrangement of the PNBU to form MIL-53 is identified as the rate-limiting reaction step responsible for the long induction time at low temperatures (<80 °C). MOF nucleation and particle growth is followed directly in-situ through a novel method—comparison of the temporal evolution of the respective FTIR and Raman bands. Analysis of the particles isolated after various synthesis times indicates that MIL-53(H2BDC) of low crystalline long-range order is formed initially, which quickly rearranges to form more ordered, crystalline particles with DMF inside of the pores (MIL-53(DMF)). It is to be expected that the synthesis steps elucidated herein can be generalized to the solvothermal synthesis of other metal–organic framework structures from metal salts and organic acid li
Keywords: Organic acids; Fourier transform infrared spectroscopy; Chemical synthesis; Metal organic frameworks; Raman spectroscopy; Bis(1; 3; 5-Benzenetricarboxylate)Tricopper(Ii); MIL-101; Metalorganic Framework; Crystalline materials; Dimethylformamide; Metals: Organic polymers; Organic solvents; Organometallics; Synthesis (chemical); Crystalline particles; Formation mechanism; Metal organic framework; N; N-Dimethylformamide; Rate-limiting reaction; Solvothermal conditions; Solvothermal synthesis; Turbidity measurements

In situ Raman and FTIR spectroscopic study on the formation of the isomers MIL-68(Al) and MIL-53(Al) - Embrechts, Heidemarie; Kriesten, Martin; Ermer, Matthias; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (RSC Advances, 2020)
The topological metal-organic framework isomers MIL-53 and MIL-68 form from similar educts but differ in their pore geometries. They have been known for several years, but their synthesis is always reported separately. In consequence, the underlying mechanism and decisive synthesis parameters leading to the formation of either MIL-53 or MIL-68 are not understood. The present study shows how to induce the formation of MIL-68(Al) rather than MIL-53(Al) at low synthesis temperatures in N,N-dimethylformamide (DMF) using a modulated synthesis approach. MIL-68(Al) is identified as the intermediate product of formic acid modulated synthesis, which converts into the thermodynamically stable MIL-53(Al) product at longer synthesis times. The interactions of formic acid with the synthesis precursors responsible for inducing MIL-68(Al) formation are investigated with in situ Raman and FTIR spectroscopy. In contrast to the commonly assumed modulation mechanism of competitive coordination of linker and modulator with the metal node, formic acid is shown to form hydrogen bonds via the carboxylic group of the terephthalic acid (H2BDC) linker, slowing prenucleation building unit and subsequent crystal growth. MIL-68(Al) formation is favored by the combination of a deficiency of terephthalic acid in solution and a slow MOF growth rate. Dissolved H2BDC in solution is proposed to hinder MIL-68(Al) formation by serving as a molecular template for the rhombic MIL-53(Al) pore channels.
CRIS-Team Scopus Importer:2020-03-17

Model development for the separation of a strongly adsorbing gas mixture on a semi-pilot scale adsorber - Vargas Schmitz, Jürgen; Kriesten, Martin; Hartmann, Martin; Kaspereit, Malte (Separation and Purification Technology, 2019)
A detailed model is developed for the separation of strongly adsorbing gas mixtures at semi-pilot scale. It assumes a non-isothermal compressible transport-diffusion mechanism in the adsorber and dispersed compressible flow in the periphery, respectively. A methodology is proposed for efficient system analysis and parameter determination, leading to high model accuracy. The separation of N-2 and CO2 on the carbon molecular sieve CMS-H2 55/2 serves as example problem. Based on experimental equilibrium data for different temperatures, the applicability of different adsorption isotherm models is investigated for the single components. Isosteric heats of adsorption and their dependency on adsorbate loadings are determined by an analysis using the virial isotherm. A single reference experiment - an adsorption-desorption breakthrough for a diluted gas mixture - allows estimating heat and mass transfer coefficients and investigating the role of competitive adsorption and heat effects. The final model accurately predicts compositions, temperatures, and flow rates for a complete set of adsorption and desorption experiments in a broad range of conditions.
CRIS-Team WoS Importer:2019-05-03

Molecular sieving of linear and branched C-6 alkanes by tannin-derived carbons - Castro-Gutierrez, Jimena; De Oliveira Jardim, Erika; Canevesi, Rafael L. S.; Silvestre-Albero, Joaquin; Kriesten, Martin; Thommes, Matthias; Celzard, Alain; Fierro, Vanessa (Carbon, 2021)
Two micro-mesoporous carbons (MMCs): a disordered mesoporous carbon (DMC) and an ordered mesoporous carbon (OMC), synthesized by an easy, low-cost, and green method are proposed as efficient hydrocarbon sieves for the separation of C-6 isomers: n-hexane (nHEX), 2-methylpenthane (2 MP) and 2,2-dimethylbutane (22DMB). Their textural characterization reveals a highly interconnected pore network within the DMC, while a reverse hierarchy of ordered mesopores only accessible through narrow micropores is found in the OMC. The pore texture strongly affects their adsorption performance by kinetic and molecular sieving effects; the narrow constrictions in the OMC allow adsorption of nHEX and partially 2 MP but not 22DMB, whereas the highly connected pore network of DMC allows adsorption of the three isomers. Multi-component adsorption isotherms calculated from the single-component experimental results by ideal adsorbed solution theory (IAST) demonstrates that the OMC material has a remarkably high selectivity for the adsorption of nHEX and nHEX + 2 MP from binary and ternary mixtures, respectively. To the best of the authors' knowledge, such behavior has never been reported so far for carbon materials. Hence, this study shows that tannin-derived MMCs have great potential to be used as an eco-friendly and low-cost alternative for the selective separation of di-branched C-6 isomers. (C) 2020 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2021-03-19

On the dynamics of gas adsorption processes for systems governed by different phenomena - Hartmann, Martin; Vargas Schmitz, Jürgen; Hovestadt, Maximilian; Kriesten, Martin; Hartmann, Michael; Kaspereit, Malte (22nd International Congress of Chemical and Process Engineering, CHISA 2016 and 19th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction, PRES 2016, 2016)

Phase Transformations in Porous Materials Studied by in Situ Solid-State NMR Spectroscopy and in Situ X-ray Diffraction - Paula, Carolin; Wisser, Dorothea; Rangus, Mojca; Schwieger, Wilhelm; Hovestadt, Maximilian; Kriesten, Martin; Vanatalu, Kalju; Oss, Andres; Org, Mai-Liis; Samoson, Ago; Hartmann, Martin (Journal of Physical Chemistry C, 2020)
Studying complex processes in solid phases such as adsorption or phase transitions in situ is the best way to obtain detailed and realistic insights on a molecular level. Besides in situ X-ray diffraction techniques, magic angle spinning (MAS) solid-state NMR spectroscopy is one of the most powerful analytical techniques. The implementation of in situ and operando MAS NMR is however challenging and requires dedicated hardware. We introduce here a new 4.0 mm wide-bore probe that allows for a continuous and well-distributed flow of gaseous adsorbates or reactants through the packed sample, as well as uniform heating of the sample and spinning of the rotor at the magic angle. The combination of both in situ MAS NMR and in situ powder X-ray diffraction allowed us to obtain new insights into two phase transformation mechanisms in crystalline, porous materials, viz. that of aluminophosphate VPI-5 into AlPO4-8 and that of metal-organic frameworks from the MIL-53 family during water adsorption and desorption.
CRIS-Team Scopus Importer:2020-10-23

Reliable surface area determination of powders and meso/macroporous materials: Small-angle X-ray scattering and gas physisorption - Schlumberger, Carola; Scherdel, Christian; Kriesten, Martin; Leicht, Peter; Keilbach, Andreas; Ehmann, Heike; Kotnik, Petra; Reichenauer, Gudrun; Thommes, Matthias (Microporous and Mesoporous Materials, 2022)
The specific surface area is key for various application fields of porous materials. Its reliable and fast determination is therefore crucial for materials development and product quality management. Surface area assessment is usually based on physical adsorption using the Brunauer-Emmett and Teller (BET) theory. However, the BET method/gas adsorption exhibits a number of limitations and challenges including (i) time consuming sample preparation and measurement time, and (ii) reliable surface areas only possible for non-porous and meso-/macroporous materials to obtain reliable surface areas. In addition, the accuracy of surface area data obtained from adsorption depends on the proper choice of adsorptive/probe. Within this context, this work evaluates in a rigorous way in-depth Small Angle X-ray Scattering (SAXS) as an alternative and complimentary approach for reliable and fast surface area assessment. To our knowledge, this work can be considered the first systematic study where the surface areas from SAXS are compared and validated with true benchmark surface area data. We utilize silica-based nanoparticles as well as a well-defined mesoporous controlled pore glass for systematic SAXS and adsorption studies (argon and nitrogen at 87 K and 77 K, respectively). Owing to the lack of micro- and narrow mesopores of these model materials, the BET method based on argon 87 K adsorption can be applied to determine benchmark surface areas. Indeed, excellent agreement was found between surface areas derived from argon 87 K adsorption and SAXS. In fact, we demonstrate that the determination of specific surface area can be brought with SAXS to a new level, where parameters such as size of the probing adsorptive, its orientation and thus its effective cross-sectional area (when adsorbed on the surface) are no longer affecting the value of the specific surface area determined. Furthermore, SAXS was shown to be significantly faster than gas adsorption. For the silica materials used, the study shows that SAXS does not require degassing and – along with analysis times of only few minutes per sample – provides an accurate and extremely fast, high-throughput approach. This fundamental study can be considered a major step in enabling SAXS for reliable surface area assessment for applications both in nanoporous materials development and quality control, thus boosting SAXS for surface area determination in general, but in particular also for materials, where the usage of gas adsorption is restricted or not possible at all.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Absolute calibration; BET Method; Gas adsorption; Small-angle X-Ray scattering; Specific surface area

Role of Prenucleation Building Units in Determining Metal-Organic Framework MIL-53(Al) Morphology - Embrechts, Heidemarie; Kriesten, Martin; Ermer, Matthias; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (Crystal Growth and Design, 2020)
While it is well-known that the particle size of solvothermally synthesized metal-organic frameworks (MOFs) can be controlled by tuning the solvent composition, which affects the solubility of the linker and metal salt educts, the exact relationship between linker solubility, initial chemical coordination steps occurring in solution, and the resulting MOFs' particle size has not yet been investigated. Here, we have studied the solvothermal synthesis of MIL-53(Al) in DMF and water/DMF mixtures with in situ Raman spectroscopy, which reveals the formation of intermediate prenucleation building unit (PNBU) species that consist of one linker molecule and one metal atom and self-assemble in solution to form MIL-53(Al). The concentration of PNBUs in solution prior to particle precipitation is dependent on the synthesis solvent ratio used and influences the MIL-53 particle size. Synthesis in pure DMF results in a high concentration of PNBUs in solution prior to MOF supersaturation and precipitation. This results in a large burst of MOF nucleation and the formation of nanosized MIL-53(Al) particles. Adding water to the DMF solution leads to reduced PNBU accumulation in solution prior to MOF precipitation due to the reduced linker solubility. The reduced accumulation of PNBUs prior to particle precipitation causes reduced nucleation and favors particle growth. The MIL-53(Al) particle size, in contrast, is independent of the MOF phase growth rate, which is highly dependent on the synthesis temperature.
CRIS-Team WoS Importer:2020-06-26

Shaping of Flexible Metal-Organic Frameworks: Combining Macroscopic Stability and Framework Flexibility - Kriesten, Martin; Vargas Schmitz, Jürgen; Siegel, Jonas; Smith, Christopher E.; Kaspereit, Malte; Hartmann, Martin (European Journal of Inorganic Chemistry, 2019)
A facile extrusion approach that can fully retain the breathing behavior of flexible metal-organic frameworks (MOF) like MIL-53 and MIL-53-NH2 employing methyl cellulose as binder is reported. Shaped MOF extrudates were extensively characterized by nitrogen sorption, X-ray diffraction, thermogravimetric analysis and scanning electron microscopy. A detailed study on the mechanical stability of MIL-53 extrudates with different amounts of binder reveals an increase in stability at low binder fractions while the maximum in attainable stability is reached at 5 wt.-% binder. In-situ XRD studies in CO2 atmosphere and under humid conditions, respectively, demonstrate the reversibility in breathing behavior of the MIL-53 extrudates without affecting the phase transition kinetics. High-pressure methane and carbon dioxide isotherms on MIL-53 and MIL-53-NH2 extrudates exhibit loadings that are comparable to the uptake of the pristine powder. The shaping approach reported herein paves the way for using flexible MOF structures in technical applications.
CRIS-Team WoS Importer:2019-11-15

Synthesis of the novel MOF hcp UiO-66 employing ionic liquids as a linker precursor - Ermer, Matthias; Mehler, Julian; Kriesten, Martin; Avadhut, Yamini; Schulz, Peter; Hartmann, Martin (Dalton Transactions, 2018)
By using a terephthalate containing ionic liquid, a new metal-organic framework, hcp UiO-66, comprising (Zr12O8(OH)(14)) double clusters and terephthalate ligands has been synthesized. The hydrothermal synthesis of hcp UiO-66 might help to establish metal-organic frameworks for industrial scale applications.